Nursing strategies for coping with the care of a potential organ donor - Silvia Silva Souza; Miriam Süsskind Borenstein; Denise Maria Guerreiro Vieira da Silva; Sabrina da Silva Souza; Juliana Bonetti de Carvalho (Universidade Federal do Ceará, 2013)
This work aimed to understand strategies that the nursing staff from an Intensive Care Unit applies to situations involving the care of a person with brain death as a potential donor. The study was conducted through qualitative, descriptive and exploratory research, carried out by 14 members of the nursing staff who work with the potential organ donor. Data were collected through semi-structured interviews, and a thematic context analysis was applied. The strategies of coping focused on emotion were: escape from reality, and reframe the event. And the strategies focused on the problem were: provide competent care, and search for other support. It is concluded that caring for a person with brain death is constituted as a very stressful event to the nursing professionals. These professionals need institutional support to better cope with these situations, because depending on how they manage their task, it may directly influence the assistance provided to patients.